Effect of Banana bract mosaic virus (BBrMV) on growth and yield of cultivar Nendran (Plantain, AAB) - and K.J. JEYABASKARAN, R. SELVARAJAN* (Indian Phytopathology, 2006)
To find the yield loss due to BBrMV in cv. Nendran (AAB), fixed field plot experiments were conducted in Tiruchirapalli District of Tamil Nadu during 1997-1999. BBrMV infected plants and symptom free healthy plants were randomly selected and tagged for recording the observations. The average yield reduction due to BBrMV was 30 per cent. The reduction in bunch weight over healthy plants was 32.7, 53.69, 30.61 and 28.84 per cent in four different fields and the variations in bunch weights of infected and healthy plants were highly significant. The yield loss varied between orchards. The yield differences between healthy and infected plants were more in fertile soil than in saline sodic, low fertile soil and from the infected plants malformed bunches of less weight, underdeveloped fingers emerged, making them not marketable.